Terjemahan Beranotasi Dongeng Le Fils À La Recherche De Sa Mère ke dalam Bahasa Indonesia - Wijaya, Elyan (UI Scholars Hub, 2019)
Annotated translation is a study that provides annotations or notes on the chosen equivalents of a number of translated words as a form of translator’s accountability. Using a comparative model, this qualitative study aims to describe the problems that were encountered when translating the source text and finding the right translation strategy to be used for addressing the existing translation problems. In this research, the source text is a children literature (tale) titled Le Fils à la recherche de sa mère by Senegalese author. The problems that were encountered when translating this tale were issues related to language and culture, such as idioms, metaphors, and cultural words. The translation problems were then addressed by using translation strategies (methods and procedures) according to Newmark (1988). In generating translations and annotations, this research referred to various dictionaries and websites. The findings of this research are expected to enrich the French children literature translations from African countries that are rarely found in Indonesia.